Formalization and Documentation: Transforming the Aceh Customary Legal System in Dispute Resolution Through Mediation - Syahputra, Muhammad Rudi; Tasrizal, Tasrizal; Ikramullah, Muhammad (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Dispute resolution through customary courts in Aceh has long been conducted by community leader (keuchik, tuha peut, and imeum meunasah) through mediation based on deliberation, consensus, and the restoration of social harmony. In the modern legal context, this living and predominantly oral mechanism faces challenges when interacting with the formal legal system, which requires written procedures, documentary evidence, and stronger institutional accountability. Purposes of the Research: This study aims to analyze how formalization and documentation transform Aceh’s customary dispute resolution system, and to explain the challenges, opportunities, and institutional model required to integrate customary mediation with the national legal framework without weakening local wisdom. Methods of the Research: The research employs an empirical juridical method with a socio-legal approach. Data were collected through literature review, observations of mediation stages and interactions in selected gampong, and in-depth interviews with experienced customary leaders, representatives of the Aceh Customary Assembly (Majelis Adat Aceh), law enforcement officials, and community members involved in customary mediation. Results of the Research: The findings reveal that Aceh has established a regulatory framework supporting customary justice through Qanun Number 9/2008, Qanun Number 10/2008, and Qanun Number 8/2019, accompanied by growing documentation practices such as written minutes and peace agreements. Formalization strengthens procedural certainty, accountability, and coordination with formal justice, but it also faces tensions arising from differences in legal culture, local customary variations, limited administrative capacity, overlapping authority, and the absence of executory legal force for customary settlements. The novelty of this study lies in formulating a flexible model of customary mediation that standardizes core procedural and documentary elements while preserving deliberation, consensus, kinship, and locally rooted sanctions as the substance of Acehnese customary justice.